Feminist designs: modernist digital humanities & Mina Loy: Navigating the Avant-Garde. Issue 3 (2nd September 2018) - Churchill, Suzanne W.; Kinnahan, Linda A.; Rosenbaum, Susan
ABSTRACT: In Part 1, we contend that design is fundamental to feminist digital humanities. "Design" refers to structures and to the process of inventing them; it also encompasses matters of style and aesthetics. If modernist studies is to thrive in a digital age, we must attend to questions of style and UX (user experience) design. To give design its due is a feminist act. It involves considering the audience's needs and interests, recognizing them as partners in the scholarly endeavor, and embracing style and aesthetics as crucial to the work of digital humanities. Feminist design also entails rethinking the processes of generating and disseminating knowledge and reinventing our scholarly methods in order to break down hierarchies, encourage open exchanges of expertise, and reflect the diversity of human creative production. In Part II, we discuss Mina Loy: Navigating the Avant-Garde, an experiment in modernist digital humanities that aims to move questions of design from the periphery to the center of scholarly attention (http://mina-loy.com/ ). Loy serves not only as a representative of women in the avant-garde, but also as a model for what digital humanists can be, if, like Loy, we dare to design radically new forms and processes.